LANGUAGE STYLE USED BY KATY PERRY AND THE HOSTS IN EXCLUSIVE INTERVIEW ON TONIGHT SHOW - Fransiska Inapaska Wuwur (Jurnal Ilmiah Spectral, 2021)
This study aims to analyze the dominant language style used by the Hosts and Katy Perry's exclusive interview on Tonight Show so that readers can distinguish the use of language styles appropriate to the situation and conditions. The type of language style that helps the researcher analyze is divided into five styles; formal, consultative, casual, and intimate styles. The research’s objective is to determine the dominant language style used by the Hosts and Katy Perry's Exclusive Interview on the Tonight Show. The researcher uses descriptive qualitative research to analyze the utterances towards a conversation on the video. This was in line with Joos's characteristics in conveying information through intonation, pronunciation, grammar, sentences, and words that correspond to each type of language style. The type of language style that is dominantly used by the Hosts and Katy Perry in the Exclusive Interview is casual style because the sentences spoken in the talk show conversations are dominant in using short and simple ones.